Intraocular Lymphoma or Infection? Subretinal Aspirate Confirms the Diagnosis - A. Saad; S. O. Salceanu; K. Oswal; A. Aboushrkh; D. Hamada (Case Reports in Ophthalmological Medicine)
Purpose. To demonstrate the importance of subretinal biopsy to reach a diagnosis when vitreous biopsy is negative or inconclusive. Methods. A 54-year-old Caucasian gentleman presented with bilateral anterior uveitis at JCUH. He initially responded to topical steroids and dilating agents. Subsequently he developed bilateral panuveitis and cataract with poor response to treatment. Detailed workup had been done to rule out infectious etiology. A suspicion of lymphoma was considered and vitreous biopsy sample was taken from one eye, which was inconclusive. Then, to help with definitive diagnosis vitreous sample, subretinal aspirate and retinal biopsy were taken. Results. Subretinal aspirate revealed Aspergillus niger. Treatment was initiated accordingly. Conclusions. Subretinal aspirate and retinal biopsy can help with diagnosis of unusual clinical panuveitis like presentation.